Efektivitas Digitalisasi Terhadap Keputusan Pembelian Online - Wiyarno Wiyarno; Erna Apriani; Indra Permana (SEIKO : Journal of Management & Business, 2023)
Technological developments in digitalization are so very rapid. Their influence is also very significant in changes and human behavior. They are starting from using the internet, social media, online transactions, and virtual meetings to increasingly sophisticated smartphones supporting all these activities. Digitalization has made changes consumer behavior in shopping change drastically. Nowadays, changes in consumer behavior in shopping have been dominated by online transactions. The average cross-generation has used and understood the use of online media, especially the millennial and gen z generations. This study analyzes the effectiveness of digital marketing, influencer marketing, and online customer reviews on purchasing decisions. The analysis method in this study is quantitative causality. The population taken is Pelita Bangsa University students, the sample taken is students belonging to the millennial and gen z generations who transact online shopping in e-commerce and marketplaces, with data analysis techniques in this study using regression double linear. The results of the data analysis that has been carried out, the first and second hypotheses are rejected, with the conclusion that digital marketing and influencer marketing do not influence online purchasing decisions. The results of the third hypothesis are accepted, with the conclusion that online customer reviews can influence online purchasing decisions in a positive direction.